Laparoscopic nephrectomy for giant ruptured renal angiomyolipoma in tuberous sclerosis: case report and literature review - Cao, Yuan; Liao, Yougang; Yan, Jiao; He, Kai; Wang, Decai; wang, Yaodong; Zhang, Tiansheng; Wang, Jianjun; Jiang, Shichun (Frontiers in Surgery, 2025)
IntroductionTuberous sclerosis complex (TSC) is an autosomal dominant disease affecting multiple organs and systems throughout the body. The rupture and bleeding of TSC-associated renal angiomyolipoma (RAML) are the most common causes of death in adults with TSC. Clinically, interventional embolization and open surgery remain the standard treatment options for RAML, with laparoscopic procedures being comparatively less utilized.MethodsThis article details the management of a 59-year-old male with TSC who presented with spontaneous rupture and hemorrhage of a large right renal RAML exceeding 15 cm in diameter. A laparoscopic right nephrectomy was successfully performed as the definitive treatment.ResultsThe laparoscopic procedure was successful in managing the acute hemorrhage and removing the affected kidney. The patient's postoperative course was uncomplicated.DiscussionThe diagnostic and therapeutic management of this complex case is discussed, along with a review of the relevant literature. This case demonstrates that laparoscopic nephrectomy can be a viable surgical option for the emergency treatment of giant TSC-associated RAML rupture and bleeding in selected patients.